Open Innovation Electronic Toll Collection Using Soft System Methodology - Tarigan, Roberto Pehulisa; Wahyudi, Andreo; Fitriati, Rachma (Manunggal Halim Jaya, 2025)
Technological developments continue to develop and expand into various fields. Indonesia began implementing non-cash payments using electronic toll technology since October 2017. This research aims to analyze the implementation of Electronic Toll Collection (ETC) on an electronic toll basis as part of technological developments in the transportation sector. Technological innovation in the form of the application of ETC has provided a number of criticisms and a big influence on PT. Jasa Marga (Persero), Tbk as the market leader in the toll road management industry in Indonesia. On the other hand, there are many benefits that can be optimized by PT. Jasa Marga (Persero), Tbk from implementing ETC. This research shows how an organization or company is able to manage the impact of open innovation into profits through the right strategy. The Soft System Methodology approach is used to analyze the complexity of implementing ETC for PT. Jasa Marga (Persero), Tbk. This research collects data in the form of facts stored in the form of research, documents and information as well as related regulations through documentation techniques. This research provides an explanation of the strategy carried out by PT. Jasa Marga (Persero), Tbk in dealing with the implementation of ETC which is explained through seven stages of SSM ETC as a new technology is obtained through open innovation. Open innovation in an organization or company can be successful if it is responded to with the right strategy. The success of an innovation is if the innovation can be accepted by all parties.